Removal of dye from textile wastewater by modified sugarcane bagass as a biosorbent - Hoang Thi Khanh Dieu; Trinh , Minh Tan Sang; Le, Nguyen Minh Nha; Ho, Thi Yeu Ly (Journal of Technical Education Science, 2017)
In this study, the sugarcane bagasse grafted with citric acid was used as a low-cost biosorbent for removal of dyes from the textile wastewater. The adsorption parameters such as initial pH values, dyes concentrations, adsorbent dosages and contact times were investigated by the batch experiments. The Freundlich and Langmuir adsorption isotherm models were used to evaluate the experimental data. The results showed that the adsorption process of dyes onto the modified sugarcane bagasse leaned towards Langmuir model for MSB and Freundlich for SB. The maximum adsorption capacity of MSB was found to be 8.40 mg/g, and at pH 9. The results showed that the modified sugarcane bagasse with citric acid could be a potential low-priced adsorbent for removal of the color from the textile wastewater.